PENGARUH BUKU AJAR FISIKA TERAPAN BERBASIS SCIENTIFIC TERHADAP HASIL BELAJAR RANAH KOGNITIF MAHASISWA - Nelfi, Nelfi; Yanti, Melda; Alim, Akbar; Riyadi, Slamet; Lelfita, Lelfita (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2025)
Applied physics is often perceived as difficult by maritime cadets due to low motivation, limited conceptual readiness, and restricted access to non-print learning materials. This study investigates the effect of a scientific-approach Applied Physics textbook on the cognitive learning outcomes of Nautical Technology students at Politeknik Pelayaran Sumatera Barat. Using a quasi-experimental nonequivalent control group design, 24 second-semester cadets were divided into an experimental group using the scientific-based textbook and a control group using conventional materials. Both groups completed pretests and posttests, and the data were analyzed using the Mann–Whitney U test with a significance level of α = 0.05. The experimental group obtained a higher mean posttest score (82.50) than the control group (80.62), and the difference was statistically significant (p < 0.05). These results demonstrate that integrating scientific inquiry steps into printed instructional materials enhances students’ conceptual understanding and supports more effective learning. The unique feature of the study is related to the fact that using a research based chemical printed textbook, addressing vocational maritime education, had not previously been investigated. Implications As reported by the results, the investigation provided a contribution to maritime physics teaching materials, they can be useful as scientific-based printed resources for enhancing and improving learning outcomes in an accessible way and context-based specificity.